2019
DOI: 10.1021/acs.energyfuels.9b02347
|View full text |Cite
|
Sign up to set email alerts
|

Ignition and Combustion Characteristics of Heptane-Based Nanofluid Fuel Droplets

Abstract: Nanofluid fuels are promising fuels in the fields of spaceflight and aviation. Their stability is a critical constraint for potential applications. Oleic acid can enhance the stability of nanofluid fuels, but it influences the ignition and combustion performance of nanofluid fuels. In this study, the effects of various concentrations of oleic acid and nanoparticles (NPs) on the ignition and combustion performance of the heptane-based nanofluid droplets were studied using a high-temperature tubular resistance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The droplet is re‐ignited. This phenomenon is also found in the studies of Gan and Han et al 12,19 Since the oxide film on the surface of the Al‐NPs is destroyed at high temperature when the flame of ricinoleic acid becomes weaker, the oxygen contacts the surface of the Al agglomerates and reacts with them so that the agglomerates emit dazzling white light. Eventually, as the reaction completes, the hot agglomerates gradually cool and the combustion is over.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…The droplet is re‐ignited. This phenomenon is also found in the studies of Gan and Han et al 12,19 Since the oxide film on the surface of the Al‐NPs is destroyed at high temperature when the flame of ricinoleic acid becomes weaker, the oxygen contacts the surface of the Al agglomerates and reacts with them so that the agglomerates emit dazzling white light. Eventually, as the reaction completes, the hot agglomerates gradually cool and the combustion is over.…”
Section: Resultssupporting
confidence: 63%
“…The breakup of the droplet is observed after the droplet expands significantly. Gan and Han et al, 12,19 also observed this phenomenon. This is because during the droplet combustion, the concentration of ricinoleic acid on the surface of the droplet will become higher and higher due to its high boiling, and it eventually forms a film region that hinders the release of vapor inside the droplet.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Nanofluids are defined as the combination of nanoparticles (1−100 nm) and base fluid, which can be classified according to the type of base liquid. 15 This section divides the base fluids into two categories (water and amine solutions). The difference between the base liquids will directly affect the absorption effect of CO 2 , and the reported base fluids are listed as follows: (1) water, deionized (DI) water; 16 and (2) amine solutions, MEA, 17 methyldiethanolamine (MDEA), 18 diethanoleamine (DEA), 19 piperazine (PZ), 20 4-diethylamino-2-butanol (DEAB), 21 2-amino-2-methyl-1-propanol (AMP), 22 triethylenetetramine (TETA), 23 and MEA−MDEA.…”
Section: Classification and Preparation Of Nanofluidsmentioning
confidence: 99%
“…The transient behaviour of the autoignition of alkane droplets has been extensively studied due to its technological interest. Both experimental [15][16][17][18][19][20] and numerical studies [21][22][23] of n-heptane, n-dodecane and n-hexadecane have revealed a catalog of exotic ignition behaviours, that includes single-stage ignition, two-stage ignition and cool flames.…”
Section: Introductionmentioning
confidence: 99%